Efeito da adição de antioxidantes na qualidade do sêmen criopreservado de bovino - GUIMARÃES, Cátia Oliveira (2011)
The function of antioxidants is control the free radicals to improve the quality of fresh and cryopreserved semen. The objective this work was to study the effect of antioxidants catalase, α-tocopherol and sodium pyruvate added in bull semen in order to control the reactive oxygen species and improve sperm quality after cryopreservation. Were used six adult Nelore bulls previously selected from other animals by evaluation of body condition and andrological examination. Semen was collected and immediately evaluated for motility and vigor at the laboratory. After, the semen were diluted with Tris-egg yolk-glycerol medium with the antioxidants molecules in different concentrations. The work was divided into four experimental groups: Group 1 (control without addition of antioxidants), Group 2 (with catalase antioxidant in three concentrations 20 IU, 80 IU and 200 IU), Group 3 (with α-tocopherol antioxidant in the concentrations of 50 mM, 100 mM and 150 mM) and Group 4 (with sodium pyruvate antioxidant in the concentrations of 1.5 mM, 3.5 mM and 5 mM). After semen thawing the computerized analysis (CASA) of motility, plasm membrane, and acrosome integrity, mitochondrial activity and measurement of thiobarbituric acid reactive substances (TBARS). It was observed that the antioxidants had no significant effect on most parameters measured, but the lower antioxidants concentrations were more efficient than the control group for the total motility, progressive motility, average path velocity, and plasm membrane integrity parameters. In the TBARS evaluation was observed lower lipid peroxidation when higher antioxidants concentrations were used. Thus more research is needed to determine the functionality of sperm, as well as indentify the optimal concentration of the antioxidants that benefits all sperm parameters after thawing.